THE ROLE OF PRAXEOLOGICAL PRINCIPLESIN SHAPING COMPETENCES OF LOCAL GOVERNMENTS - Kisała, Magdalena (Review of European and Comparative Law, 2017)
Local governments act based on and within legal boundaries . They realize objectives which stem from law as well . In order for law to facilitate the actual realization of specific objectives, when designing and executing it, a rational legislator ought to take into account praxeological principles . The principles influence the division of tasks and allocation of competences to proper local government bodies . As a result, they contribute to their efficient operation, shape structures the bodies function in, and determine the ways these structures operate in .